O ensino-aprendizagem de língua-cultura inglesa no Sistema de Organização Modular de Ensino (SOME) – crenças em (dis)curso - FURTADO, Geciel Ranieri (2023)
In this Final Coursework (TCC), entitled The teaching-learning of the English LanguageCulture in the System of Modular Organization of Teaching (SOME) - beliefs in (dis)course, we propose to investigate the statements of riverine students about the teaching-learning of English Language-Culture, considering their beliefs as constituents of and in their subjectivities and ways of life among forests and rivers around the city of Cametá-PA, tracing the emerging effects of meaning. The research aims to investigate the representations of riverside students in the context of High School (SOME) about the English Language-Culture. The theoreticalmethodological path took place through Discourse Studies considering Foucault (1996, 2007); Coracini (2007, 2016); Orlandi (1999); Lopes (2018, 2020); to move the concept of identity, we rely on the theoretical assumptions of Bauman (2013) and Hall (2005); to approach about beliefs, we reflect from the proposal of Barcelos (2004) and Silva (2005), and thus build the basis of the research. In order to gather data, we conducted an interview with riverside students from the locality of Mutuacá de Baixo, Cametá/PA, who study in the SOME modality. In the analyses performed, the riverside people reveal that their constituent beliefs influence (n)the teaching-learning process of English Language-Culture for riverside people, being responsible for creating resistance in the students to its learning.